PHONOLOGICAL SYSTEM OF BANGKA MALAY LANGUAGE, TOBOALI DIALECT, IN SOUTH BANGKA REGENCY - Herland Franley Manalu; Bob Morison Sigalingging; Dini Wulansari (Journal of Applied Linguistics and Literature, 2021)
The factors that led to the extinction of a regional language dialect are the absence of inputting the vocabulary into a dictionary, recording the phonological system to academic articles, and the absence of language enthusiasts or linguists who want to maintain the existence of a dialect in a community. Therefore, this study aims to analyze the phonological system in the Toboali dialect as the variant of the Malay language in the South Bangka Regency. The research is triggered by the decreasing use of regional languages in society and it purports to identify and describe the phonological system of the Toboali dialect. To do that, this study uses a qualitative method in which the researchers firstly collected data, then analyzed and classified the data, and finally drew a conclusion. The Swadesh list which consists of 250 vocabularies was utilized during the interview. The researchers obtained the Toboali dialect words by gesturing or pointing to objects and images so the informants were able to pronounce the words and then the phonetic transcription could be written. Thus, the data obtained are accurate because the language obtained was not delivered in Indonesian but is purely pronounced in the Toboali dialect. The results of this study indicate that there are 7 vowels: [?], [e], [o], [i], [?], [?], [a] and 19 consonants are found in the Toboali dialect: [b], [c], [d], [f], [g], [h], [j], [k], [l], [m], [n], [p], [r], [s], [t], [w], [y], [z], and [?].